The Plio-Pleistocene development of Atlantic deep-water circulation and its influence on climate trends. (1st September 2015) - Bell, David B.; Jung, Simon J.A.; Kroon, Dick
Abstract: Using benthic stable isotope records from 10 sites in the Atlantic Ocean, including two new records from Walvis Ridge in the Southeast Atlantic (Sites 1264 and 1267), we review changes in Atlantic deep-water circulation in the context of Plio-Pleistocene climate. Overall, we find non-linear responses of Atlantic deep-water circulation to a cooling climate, with differently evolving glacial and interglacial states. Our main conclusion is that peak North Atlantic Deep Water (NADW) production was reached between ∼2.0 and 1.5 Ma, most prominently seen by a maximum in ventilated (high δ 13 C) conditions in the mid-depth Southeast Atlantic (Site 1264). We infer that a major source of NADW at this time was the export of dense overflow water from the Nordic Seas into the abyssal East Atlantic. Sea surface temperature records from the North and South Atlantic support this notion and indicate that the peak NADW production between ∼2.0 and 1.5 Ma was compensated by a stronger warm surface-water return flow (i.e. Atlantic Meridional Overturning Circulation (AMOC) was enhanced), causing long-term (>10 5 year) heat piracy from the South to the North Atlantic. In the wider picture of Plio-Pleistocene climate evolution, we find that a long-term enhancement in the average state of AMOC (∼2.4–1.3 Ma) coincides with the "41-kyr world". Hence, we speculate that the transitory negative feedback response of enhanced AMOC to a cooling climate supplied heat to key areas of ice-sheet growth, acting to limit their size and maintain the "41-kyr world". Once a threshold in global cooling was reached, the strength of AMOC lessened, providing a positive feedback for the Early-Middle Pleistocene Transition and the associated build-up of northern hemisphere ice-sheets. Highlights: Deep-water changes are reconstructed using a suite of δ 18 O and δ 13 O records. Peak Plio-Pleistocene AMOC was reached between ∼2.0 and 1.5 Ma. A long-term enhancement of AMOC occurred between ∼2.4 and 1.3 Ma. AMOC acted as a regionally important negative feedback during global cooling. Enhanced AMOC may have helped maintain the "41-kyr world".